Statistical Convergence in Paranorm Sense on Time Scales: Tuba Gulsen, Hikmet Koyunbakan, Emrah Yılmaz, Yavuz Altın - Team, Support (Thai Journal of Mathematics, 2022)
In this study, we define statistical convergence and lamda-statistical convergence in paranorm sense on anarbitrary time scale equipped with paranorm. Furthermore, we study on strongly lamda_p-summability on timescales in paranorm sense. Eventually, some inclusion theorems are proved.